Acute kidney injury in cardiogenic shock: A comprehensive review. Issue 1 (29th July 2020) - Sheikh, Omar; Nguyen, Tung; Bansal, Shweta; Prasad, Anand
Abstract: Acute kidney injury (AKI) is an ominous predictor of mortality in cardiogenic shock. The present review examines the pathophysiology of AKI in cardiogenic shock (CS), summarizes the pertinent literature including the diagnostic criteria/definitions for AKI and possible role of biomarkers, and identifies risk factors and possible therapeutic interventions for AKI in CS. Our review finds that AKI is common in patients with CS and is associated with increased morbidity and mortality. Urinary biomarkers of renal tubular injury appear more sensitive for detection of AKI but have yet to be incorporated into daily practice. Emerging data would suggest vasopressor choices, mechanical circulatory support, and renal replacement therapy may have important therapeutic roles in the management of CS.